Implementasi Kampus Merdeka: Implikasi pada Mahasiswa Perguruan Tinggi Negeri di Aceh Barat - Nila Safrida (Pencerah, 2021)
Learning outside of the study program is one of the programs offered by the Independent Campus Policy, which is a new policy in the field of education. The study will concentrate on student exchange programs, internships, and village development, all of which should be evaluated for their feasibility. This study employs a qualitative technique using a case study approach, and the research indicator is David C. Korten's theory of compliance. The findings suggest that not all PTNs in West Aceh have adopted the Merdeka Campus. Although the Merdeka Campus policy has been designed to meet the demands of students, students have complained about rising living costs and the lack of precise criteria for each activity. The implementing organization in charge of the program is ineffective because there are still activities without a competent agency. The target group, students, believe that the program's implementing organization is inconsistent in formulating and issuing policies, which has a detrimental influence on students. It can be concluded that PTN has attempted to implement the independent campus policy in West Aceh, and that this is viewed positively by students; however, improvements are required so that the results of the implementation of an independent campus can provide the best results for improving the quality of higher education in West Aceh.